Electrification of Steam and Thermal Oil Boilers in the Textile Industry: Techno-Economic Analysis for China, Japan, and Taiwan - Ali Hasanbeigi; M. Jibran S. Zuberi (Energies)
Process heating is typically more than half of the total final energy demand in the textile industry, most of which is usually provided by fossil fuels. There is significant potential to decarbonize the textile industry by the electrification of process heating where low-carbon electricity is used. This study aims to quantify the potential for the electrification of process heating in the textile sector in three of the top textile manufacturing and exporting countries in the world. The results show that the total annual potential energy savings due to the electric steam boiler applications are estimated to be around 92, 2.4, and 2.5 PJ in China, Japan, and Taiwan, respectively, by 2050. This is equal to approximately 19% of the total boiler energy demand in the three economies. Similarly, annual potential energy savings of 8.6, 0.21, and 0.24 PJ can be realized if the existing fossil-fuel-fired thermal oil boilers are electrified in the textile industry in China, Japan, and Taiwan, respectively, by 2050. Moreover, the potential CO2 abatement resulting from the electrification is highly dependent on the carbon intensity of the electricity used. The economic analysis shows that switching from combustion boilers to electric boilers may result in higher energy costs primarily because the average electricity prices in all three economies are substantially higher than fossil fuel prices. Finally, some key recommendations that different stakeholders can take to scale up electrification in the textile industry are provided.